Ergonomic observation : working environment on health problem (MSDs) among older fisheries community at Muar Johor, Malaysia - Md Yusoff, Irwan Syah; Md Ishak, Siti Mastura; Mohd Upandi, Rafidah (Consumer and Family Economics Association, 2021)
Older fisheries communities are classified as vulnerable groups with many diseases. This paper aimed to determine the impact of working tasks on safety and health among the older fisheries community at Muar, Johor through ergonomic observation. A cross-sectional study was conducted, and simple random sampling was used for data collection online. The sample size was 200 respondents from nine places involved in the fishery sector at Muar, Johor. Data were collected through a self administered questionnaire. Data were analyzed using an SPSS software version 2.0 based on inclusive criteria. The findings show the older fisheries workers were highly potential to expose to Musculoskeletal Disorder (MSDs) when performing the working task. Therefore, older communities in the fisheries industry are encouraged to practice working tasks using an ergonomic approach to perform healthy work. From a Malaysian perspective, the implication of low awareness of ergonomics education could reflect the quality of lifestyle and health among older fisheries workers in Muar, Johor. Further research should involve all fisheries stakeholders from Malaysia's region to understand the safety of a healthy working environment for a better quality of life.